Quantifying defensive performance in football: A piecewise parametric survival approach to goal scoring time - Dutta, A.; Gogoi, J.; Bhattacharjee, D.; Saikia, H. (International Journal of Sports Science & Coaching, 2025)
To a significant extent, strategy deployment in sports has become data-driven. This has given rise to the application of data analytics in different sports, and football is no exception. This paper models the performance of selected national football teams, ranked among the highest in the FIFA standings as of June 2023, while playing against significantly lower-ranked opponents (minnows). When minnows play a relatively stronger team, their prime concern is not to concede a goal, thereby organising a deep defensive line, making it difficult for the more vigorous opposition to score. Thus, considering the time to the first goal scored by a stronger team as a time to an event, parametric survival analysis is applied in this study to compare the performance of stronger football teams against minnows. The study finds that the hazard function is neither a monotonic function nor a bathtub curve; instead, it takes a zig-zag form. This calls for a piecewise fitting of the survival distribution, which provides a better fit than any standard survival distribution proposed in the literature. By fitting such piecewise survival curves for each selected national side, one can identify sides that can better handle the minnows in football.